Pelatihan Menulis Esai Destinasi Wisata sebagai Upaya Pemberdayaan Masyarakat untuk Mempromosikan Potensi Wisata di Gunung Kidul - Cahyaningrum Dewojati; Sugihastuti Sugihastuti; Ramayda Akmal; Wira Kurniawati (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2023)
This community service activity aims to empower the community to write essays containing the introduction and promotion of tourism potential around Gunungkidul Regency. Gunungkidul is a district in the Special Region of Yogyakarta which has a lot of tourism potential, ranging from nature (such as beaches, caves, lakes, forests, hills, etc.), culture (culinary, performing arts), to historical sites, and so on, which developed by the government and private stakeholders. The target community for this workshop are members of the Pelita Gunungkidul Community whose members are educators who are also writers and literacy activists in Gunungkidul. The number of participants in this activity was 34 people. The method used is the lecture method to provide material, questions and answers, discussions, direct guidance during the writing process, both offline and in bold, and the editing process for participants' writing. The results obtained are an increase in participants' writing skills, mastery of essay material, increased understanding of tourism potential in the Gunungkidul area, and a joint anthology book with ISBN containing travel essays written by workshop participants. The book will then be distributed more widely to the people of Yogyakarta and its surroundings.